Climate Change and Agriculture: Impacts, Adaptation, and Mitigation - Rosegrant, Mark W. (2023)
Rosegrant, Mark. 2023. Climate Change and Agriculture: Impacts, Adaptation, and Mitigation. PowerPoint presentation given during university-wide seminar. Texas State University, San Marcos, Texas, March 30, 2023.